Wstępna informacja o kaflach z Piotrkowa Trybunalskiego ze szczególnym uwzględnieniem zespołu pozyskanego w trakcie badań archeologicznych przeprowadzonych w 2005 roku - Długoszewska, Wiktoria; Pietrzak, Janusz (Acta Universitatis Lodziensis. Folia Archaeologica, 2010)
The present text contains essential information about a collection of stove tiles obtained during archaeological excavations conducted in the area of historical town of Piotrków Trybunalski and its suburbs. It consists of four parts. In the first the authors present the range of research works – both stationary ones and supervisions undertaken on the occasion of various earthworks – carried out in the area since 1962. The second part of the text is devoted to a concise presentation of research results in the area of the Jesuit church and monastery built on the turn of the 17th and 18th centuries. Whereas, the third part discusses collections of stove tiles found in Piotrków Trybunalski during older research works, and in the last, fourth part a preliminary characteristics of the collection obtained in the course of the works conducted in 2005, including nearly 13 000 tile fragments, mainly formed in matrixes was presented. However, it is very varied material, which presents technological and stylistic features commonly known and spread in tile-making in Poland, especially in the area of widely understood Great Poland province, covering proper Great Poland, Kuyavia and central Poland. In the collection tiles with Renaissance-mannerism and early Baroque stylistics prevail, however, there are also artifacts both older and younger, therefore the whole may be considered representative for the period from 15th/16th centuries to the 20th century.